Abuse Against Children: Analysis of the Causes, Impact, and Legal Protection for Victims Based on Child Protection Law - Pradini, Yustia Okta; Simanungkalit, Jason A.R.; Hosnah, Asmak Ul (PT FORMOSA CENDEKIA GLOBAL, 2024)
Persecution is an arbitary act against other person with the aim of torturing and intentionally causing pain and injury. An abuse can be happened to anyone, especially to a child. Child abuse is a serious problem and it is requires more attention on the legal aspect. Persecution is an act that against the law and is contrary to the implementation of human rights, where all humans have their right to lives. This research aims to analyze thr causes, impacts, and legal protection toward children whose a victim of children abuse. By using a normative legal approach with a normative juridical approach methods which is carried out by examining theories, concepts, and related legislations.